No Fear of Ridicule – Deploying Plaything Technology for Credible Representations of Urban Landscape. (March 2014) - Rekittke, Joerg; Ninsalam, Yazid; Paar, Philip
As technology affine urban landscape architects, working in Asian mega cities, we conduct research on urbanity beyond prime premises and nice neighbourhoods with maximum tourist potential. We roam through crowded and super narrow, widely informal city layouts, where we apply our digital fieldwork equipment and conduct design work. In these places we test low cost cameras and camera drones, tools that had been developed as documentation equipment for outdoor sportspersons respectively playthings for all the world. Technically limited, if not insufficient and physically labile, these basic tools help us to experiment in the field without problematic loss risks and without scaring people on site. In this paper, we describe a method of on-site data and image gathering, which allows the processing of 3D models of labyrinthine informal city spaces. The result of our study is a three-dimensional puzzle of sufficient precision, making a widely inaccessible and undocumented piece of city terrain visible, understandable and designable.